Augmented Reality Virtual Guide Museum Multatuli Rangkasbitung Based on Android - Karyaningsih, Dentik; Fernando, Donny; Sofian, Agus Rulli; Luthfi, Fuad (Universitas Trilogi, 2022)
Multatuli Museum has been established for several years and is visited by many tourists. However, in practice the Multatuli Museum often lacks museum guides when there is an increase in visits, so that visitors who are not accompanied by a tour guide do not get complete information. In addition, the lack of interest of the younger generation in visiting museum attractions so that by applying Augmented Reality technology to the Multatuli Museum is expected to attract visitors, especially the younger generation. Augmented Reality (AR) is a technology that is able to insert 3D and 2D objects into a real environment in real-time to display a Virtual Guide at the Multatuli Museum. The author creates an animation in the form of a virtual guide for the Multatuli Museum using Blender software to create 3D animations and using Unity software to build the application as well as the Vuforia extension for Unity with C# programming language. The author uses the prototyping method as the application development method and uses the Unified Modeling Language (UML) as the system design. This research produces an Augmented Reality Application that can be used on Android smartphones. This application is capable of displaying 3D animations that provide information about the showrooms in the Multatuli Museum. Based on black box testing all features in the application are 100% running well. with this application visitors feel helped when the tour guide is limited and feel happy because there is still a Virtual tour guide who helps in the museum.